Peptides contained in the composition of Laennec that contribute to the treatment of hyperferritinemia and iron overload disorders - O. A. Gromova; I. Yu. Torshin; V. A. Maksimov; A. G. Chuchalin; V. G. Zgoda; А. N. Gromov; O. V. Tikhonova (Фармакоэкономика)
Introduction. Hemosiderosis is a pathologic condition that accompanies liver, lung, and other organ diseases. Polypeptide-containing drug Laennec contributes to the elimination of excessive iron deposits in tissues.Aim. The study was aimed to identify peptides contained in the composition of the drug that take part in the regulation of iron homeostasis and correction of hemosiderosis and hyperferritinemia.Materials and Methods. The study of the drug composition was conducted with hybrid mass-spectrometry and modern methods of analysis of Big Data based on the topological approach to recognition.Results. The preparation contains 19 peptides that are potentially important for the regulation of iron homeostasis. These peptides help to treat the disorders of iron metabolism by regulating the levels of the main hormone of iron homeostasis hepcidin by reducing the synthesis of ferritin and by exhibiting anti-inflammatory and immunomodulatory effects.Conclusion. The identified peptides allowed the authors to describe the molecular mechanisms of the iron overload elimination that are known from experimental and clinical studies of the analyzed polypeptide drug.